Factors Influencing Self-Identity and Menopausal Symptoms on Level of Depression in Middle Aged Women - Mi Jeong Han; Ji Hyun Lee (Korean Society of Women Health Nursing, 2013)
PURPOSE: The purpose of this study was to identify the factors influencing self-identity and menopausal symptoms their influence on level of depression in middle-aged woman. METHODS: Participants were 135 middle-aged women who were living in city B, were 45-60 years old, informed of study purpose, and agreed to participate. Data were collected from December, 2012 to January, 2013 using scales measuring depression, self-identity, and menopausal symptoms. Data were analyzed using t-test, ANOVA, Scheffe test, Pearson Correlation Coefficients, and Multiple Stepwise Regression. RESULTS: Level of depression was low, self-identity was slightly high, and menopausal symptoms were relatively low in these middle-aged women. There were significant differences in depression by perceived health status and perceived economic status. Depression had a moderate negative correlation with self-identity (r=-.49, p<.001) and a moderate positive correlation with menopausal symptoms (r=.57, p<.001). Menopausal psychological symptoms were the factor most affecting depression and explained 37% of the variance in depression. A total of 51% of variance in depression was explained by menopausal symptoms (psychological and physical), self-identity, and perceived economic status. CONCLUSION: Thus, an effort to improve self-identity, especially a plan to attenuate menopausal psychological symptoms is needed to reduce depression.